Os livros didáticos produzidos durante a ditadura militar brasileira e a ditadura de Stroessner no Paraguai: o ensino de história e as versões da Guerra do Paraguai (1959- 1983) - Bruna Reis Afonso (2017)
This dissertations goal is analyze and compare the versions of Paraguays war from didactic books published among the military civilian dictatorship in Brazil (19641985) and the Stroessners dictatorship in Paraguay (1954-1989). The temporal delimitation that guides this research comprehend the time between the years of 1959 and 1983. This delimitation was chosen from the search sources, based on the dates from the didactic books publication, selected to compose our documental corpus. We were looking for the comprehension of the political e pedagogical conceptions that guided the educational reforms made during the Brazilians and Paraguayans dictatorship. It was persued too, analyse how the contents related to the History was mobilized in the curriculum, which assumptions and purposes conducted the history of Brazil and Paraguay. In related to the history of Paraguays War, the main focus was the comprehension through quantitative aspects, which space the narrative about the conflict occupied in the studied books, through the quantitative aspects. Beyond to evidence the way which every book developed a narrative about the conflict, it was seeked, capture what were the influences from the political and pedagogical context, on the narratives, analyzing the discursive strategies used on them. It was analyzed not only the text, but also the images, fastening exercises, the editorials resources like Caps Lock and colors, which are use to try direct the reader to fix determined information and the apprehension of a determined perspective about the conflict, the nations past, the acting of the armed forces, of the political and military leaders, etc. We emphasize what differentiates and resembles the narratives about the War, produced in Brazil and Paraguay.